Evaluasi Kinerja BFPT Unit 6 PLTU Suralaya Pasca-Overhaul - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Alamsyah Robby Maulana (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
Boiler Feed Pump Turbine (BFPT) is a critical auxiliary component in steam power plants because it supplies feedwater from the deaerator to the boiler steam drum through the heater system. Continuous operation may reduce pump performance due to leakage, wear, seal damage, abnormal noise, and internal component deterioration. This study evaluates the performance of BFPT Unit 6 at PLTU Suralaya before and after overhaul using performance test data from December 2019 and February 2020. The evaluated parameters include flow rate, suction and discharge velocity, total head, hydraulic power, and pump efficiency. The calculation uses the continuity equation, Reynolds number, head losses, total head, hydraulic power, and pump efficiency. The results show that overhaul increased the efficiency of both BFPT units. BFPT A efficiency increased from 68.98% and 70.00% before overhaul to 72.01% and 73.50% after overhaul. BFPT B efficiency increased from 69.31% and 71.10% to 72.05% and 74.20%. The increase was associated with lower total head and restored mechanical condition after mechanical seal replacement and inner-part repair. Therefore, overhaul improved BFPT performance and should be supported by routine monitoring of leakage, vibration, lubrication, and operating flow.